Relationship between Islamic Stock Prices and Macroeconomic Variables: Evidence from Jakarta Stock Exchange Islamic Index - Muhammad Rizky Prima Sakti; MD. Yousuf Harun (Global Review of Islamic Economics and Business, 2013)
This paper attempts to analyze the relationship between Jakarta Stock Exchange Islamic Index (JII) and selected macroeconomic variables namely exchange rate, industrial production, inflation rate, and money supply. We used monthly data from January 2000 toDecember 2010.The methodology used in this paper is time series techniques of co-integration and vector autoregression (VAR). In the analysis, we rely on variance decompositions and impulse-response functions to capture the strength of interactions among variables. The results revealed that there is co-integration between Islamic stock prices and macroeconomic variables. Specifically, Indonesian Islamic stock market are driven more by domestic factors. These macroeconomic factors considered to be emphasized as the policy instruments by the governments in order to stabilize Islamic stock prices.